Usaha Pemasaran Produsen Tempe - R. Nana Kusdiana; Trias Septyoari Putranto (Bina Nusantara University, 2013)
Tempe is a food made from the fermentation of soybeans or some other materials using somekind of fungus Rhizopus, such as Rhizopus oligosporus, Rh. oryzae, Rh. stolonifer or also known as bread mold, or Rh. arrhizus. Fermentation preparations are commonly known as